Analysis of the information by the management of security incidents in organizations - Tasa-Catanzaro, María Elena (2022)
Security incidents in an organization are considered the main source for evaluating the correct application of security controls in public or private organizations. The investigation is based on the behavior of the incidents before the participation of information technology controls together with the formal processes in the organizations. Good security practices based on the international standards ISO / IEC 27001 and ISO / IEC 27002 were used. The Magerit v3 methodology and business intelligence techniques were applied to integrate and process the information obtained through heterogeneous sources of information implemented in the organizations under study. The information obtained was established in 9 security controls common to the organizations under study applied under an experimental study. The analysis of the arrival data will establish that the constant monitoring and supervision of the application of the security controls raises the security levels in the organizations that guarantee the continuity of the services and processes.